2015
DOI: 10.1016/j.ebiom.2015.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Catastrophe in Mice Lacking Transferrin Receptor in Muscle

Abstract: Transferrin receptor (Tfr1) is ubiquitously expressed, but its roles in non-hematopoietic cells are incompletely understood. We used a tissue-specific conditional knockout strategy to ask whether skeletal muscle required Tfr1 for iron uptake. We found that iron assimilation via Tfr1 was critical for skeletal muscle metabolism, and that iron deficiency in muscle led to dramatic changes, not only in muscle, but also in adipose tissue and liver. Inactivation of Tfr1 incapacitated normal energy production in muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 51 publications
7
52
0
Order By: Relevance
“…Genetic ablation of TFR1 in mice demonstrates the importance of the Tf endocytic cycle for iron import into erythroid cells (Levy et al, 1999) as well as cardiomyocytes (Xu et al, 2015), muscle cells (Barrientos et al, 2015), and dopaminergic neurons (Matak et al, 2016); combined immunodeficiency in patients with a Y20H substitution in TFR1 also reveals a role of TFR1 in B and T cells (Jabara et al, 2016). However, most non-erythroid tissues can develop without TFR1 (Li et al, 2009; Ned et al, 2003), showing that Tf-independent routes of iron acquisition exist.…”
Section: Rolling Out the Red Carpet: Iron Metabolism In Erythroid Cellsmentioning
confidence: 99%
“…Genetic ablation of TFR1 in mice demonstrates the importance of the Tf endocytic cycle for iron import into erythroid cells (Levy et al, 1999) as well as cardiomyocytes (Xu et al, 2015), muscle cells (Barrientos et al, 2015), and dopaminergic neurons (Matak et al, 2016); combined immunodeficiency in patients with a Y20H substitution in TFR1 also reveals a role of TFR1 in B and T cells (Jabara et al, 2016). However, most non-erythroid tissues can develop without TFR1 (Li et al, 2009; Ned et al, 2003), showing that Tf-independent routes of iron acquisition exist.…”
Section: Rolling Out the Red Carpet: Iron Metabolism In Erythroid Cellsmentioning
confidence: 99%
“…Genetic deletion of TFR1 is embryonic lethal (62). Tissue-specific knockouts showed that TFR1 is required for normal iron metabolism in skeletal muscle (63) and cardiomyocytes (64) and that TFR1 serves an unidentified iron-independent function in intestinal epithelial cells (65). Transferrin receptor 2, largely restricted to the liver and erythroid precursors (66), also interacts with holotransferrin but does not substantially contribute to iron uptake (67), acting primarily as sensor of systemic iron status (41).…”
Section: Transferrin and Transferrin Receptorsmentioning
confidence: 99%
“…TfR1 deficiency in erythroid cells results in anemia caused by a hemoglobinization defect. In nonerythroid cells, iron defects resulting from TfR1 deficiency result in metabolic defects, defective mitophagy, and increase in gene expression associated with cell death (16,17). A noncanonical function for TfR1, not related to iron metabolism per se, has been recently reported in some tissues (15,18).…”
mentioning
confidence: 99%
“…Loss of Fpn function in several cell types causes iron overload (11,12) and has been implicated in myelination defects (13). TfR1-mediated iron uptake is the main source of iron for actively proliferating cells, and is essential for iron transport in erythroid cells and neural tissue (14), epithelial enterocytes (15), skeletal muscle (16), and cardiac muscle (17), in addition to DA neurons, as described in Matak et al (6). TfR1 deficiency in erythroid cells results in anemia caused by a hemoglobinization defect.…”
mentioning
confidence: 99%